A glasshouse of stars - Marr,Shirley (United Kingdom: Usborne Publishing Limited, 2021)
A Glasshouse of Stars is a heartfelt and magical realist novel that follows Meixing Lim, a young girl who migrates with her family to a new country in search of a better life. After arriving, Meixing struggles with the challenges of fitting into unfamiliar surroundings$1 (Bnew customs, a new language, and a new school where she often feels out of place. The family moves into a mysterious house left to them by a distant relative. This house seems alive, shifting and changing in response to Meixing$1 (Bs emotions, fears, and hopes. In its glasshouse, time and memory blend together, helping Meixing understand her past and present. As she navigates loneliness, loss, and cultural adjustment, the glasshouse becomes a safe space where she can face her grief and find strength. With the help of her new friends$1 (Bparticularly a kind boy named Kevin and a brave girl named Josh$1 (BMeixing slowly gains confidence and learns to cope with the difficulties her family faces. The story explores themes of immigration, belonging, friendship, and resilience. Through magical elements and emotional depth, the book beautifully portrays the inner world of a child finding her place in a new life.s
A Glasshouse of Stars is a beautifully written novel that blends emotional realism with gentle magical elements to explore the experience of immigration through a child$1 (Bs eyes. The story sensitively portrays the challenges of adjusting to a new country$1 (Blanguage barriers, cultural differences, loneliness, and the pressure to fit in$1 (Bwhile also celebrating the strength, courage, and hope that help young people overcome these difficulties. The living, shifting house serves as a powerful metaphor for Meixing$1 (Bs emotions, symbolizing how grief, fear, and resilience shape one$1 (Bs inner world. Through vivid storytelling and heartfelt moments, the book highlights themes of family, healing, identity, and the importance of supportive friendships. It encourages readers to empathize with newcomers and appreciate the emotional journey behind every child finding their place in a new environment. Overall, the novel is a touching and imaginative exploration of growth, belonging, and the power of holding on to hope even in difficult times.s
Keywords: Immigration; Belonging